Hepatitis C virus seroprevalence in adults in Africa: a systematic review and meta‐analysis. Issue 4 (19th October 2015) - Riou, J.; Aït Ahmed, M.; Blake, A.; Vozlinsky, S.; Brichler, S.; Eholié, S.; Boëlle, P.‐Y.; Fontanet, A.; ,
Abstract: With the introduction of more efficient treatments for hepatitis C virus (HCV), improved epidemiological information is required at the country level to allow evidence‐based policymaking for elaboration of national strategies and HCV resources planning. We present a systematic review with meta‐analysis of HCV seroprevalence data in adults in African countries. We conducted a systematic review of all HCV seroprevalence estimates reported in African countries from 2000 to 2014 in MEDLINE, AJOL and grey literature. We assessed studies performed in the general population and among blood donors, pregnant women and HIV‐positive patients. A meta‐regression analysis was used to provide adjusted estimates of HCV seroprevalence in the general adult population in each country, accounting for the heterogeneity in sample age structure and population types in the included studies. We identified 775 national‐level estimations, among which 184 were included. Estimates of HCV seroprevalence were produced for 38 countries, in addition to the results from nationwide representative surveys available in Egypt and Libya. Next to Egypt, which clearly stands out, the highest levels of seroprevalence were found in Middle Africa (e.g. Cameroon, Gabon and Angola) and some West African countries (e.g. Burkina Faso, Benin), and the largest absolute numbers of infected adults were found in Nigeria, Ethiopia and Democratic Republic of Congo. This study exposes the diversity of HCV epidemiology among African countries. Egypt and several countries of West and Middle Africa present a HCV burden that will require strong governmental commitment to promote efficient preventive and curative interventions.